Microscopic investigation of incipient basalt breakdown in soils: implications for selecting products for enhanced rock weathering - Burke, Tarrah M.; Kamber, Balz S.; Rowlings, David (Frontiers in Climate, 2025)
Digital optical and scanning electron microscopy (SEM) was used to study advance of incipient weathering of basaltic rock particles for two enhanced rock weathering (ERW) sites in Eastern Australia and three natural basalt sites (New Zealand and Eastern Australia). At the ERW sites, weathering of amended rock particles (up to 8 mm in diameter) induced a significant increase (1–1.5 pH unit) in shallow soil pH. After 14 months of incubation at the more recent site, 6–8 mm basalt particles showed dissolution of glass and olivine while pyroxene and plagioclase remained largely fresh. No secondary minerals were identified by SEM and high-quality X-ray diffraction analysis. Compared to the fresh, quarried basalt, the measured specific surface area (SSA) increased by 33%, suggesting microporosity formation via dissolution. At the >20 years ERW site, results were complex because of inconsistent application of basalt and greenschist facies ‘metabasalt’. Metamorphic rock particles showed negligible weathering while basalt particles could only be identified in the coarse (>6 mm) fraction of the shallowest (0–5 cm) soil. Within the finer particles in the deeper (5–10 cm) zone of elevated pH, potential ‘ghost’ basalt particles were identified by distribution patterns of ilmenite, suggesting near-complete basalt breakdown of mm-sized particles on decadal timescale. In variably weathered natural samples, dissolution also dominated over precipitation of secondary phases. Weathering progress in basaltic tephra deposited 150–600 years ago strongly depended on emplacement context. Tephra in free-draining >10 cm thick lapilli beds was only weakly altered, even where covered by soil, likely due to lacking connectivity of fracture networks for water access. In all studied incipiently weathered particles, we found sequential breakdown of glass and olivine before attack of pyroxene and plagioclase. Recognisable secondary mineral formation was minimal, but SSA increased over least weathered particles. The presence of interconnected glass and fracture networks apparently aids the rate of incipient weathering, increases microporosity and promotes particle disaggregation. This may permit application of relatively coarse (>5 mm) basalt for ERW but only for potential amendments where microscopic investigation and SSA have established suitable weathering fluid access networks.